2015
DOI: 10.1093/intqhc/mzv024
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between accessibility of healthcare facilities and medical care utilization among the middle-aged and elderly population in Taiwan

Abstract: Our study of Taiwan's experience could provide a valuable lesson for countries that are planning to launch universal health insurance system, locate budgets in health care and transportation. The middle-aged and elderly who were facing more challenges in accessing health care, no matter in perceived accessibility or real time to access health care, had less outpatient visits and more drug stores shopping. Strategic policies are needed to improve accessibility in increasing patients' perception on access and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…48 Higher income may be an indicator of healthier living habits, 49 more physical activity, 49 and better access to healthcare services. 50 Previous study results showing that economic status influenced women more than men in terms of health and access to healthcare were also confirmed in this study. [51][52][53][54] Also, the results of the study corresponded with those of previous studies that found as the socioeconomic status of family income is lower, women were more likely to have osteoporosis.…”
Section: Discussionsupporting
confidence: 86%
“…48 Higher income may be an indicator of healthier living habits, 49 more physical activity, 49 and better access to healthcare services. 50 Previous study results showing that economic status influenced women more than men in terms of health and access to healthcare were also confirmed in this study. [51][52][53][54] Also, the results of the study corresponded with those of previous studies that found as the socioeconomic status of family income is lower, women were more likely to have osteoporosis.…”
Section: Discussionsupporting
confidence: 86%
“…Recent cross-sectional analyses showed an association between perceived access and health care use in Taiwan [35]. For Germany, objective accessibility, measured as ratio of number of physicians and population, was not associated with GP visits nor specialist visits [4].…”
Section: Discussionmentioning
confidence: 99%
“…This database reimburses approximately 99.7% of national health care services; its data include hospital and medical professional staff characteristics and subject's enrolment and medical information. This database has been shown to re ect the accessibility of health care facilities and medical care utilization [55,56]. The medical information collected includes diagnosis, procedure, medication, medical cost, and date of visit [57].…”
Section: Data Access and Cleaning Methodsmentioning
confidence: 99%